(untitled) (Research, Society and Development, 2025)
The objective of this article is to provide a structured and well-founded analysis that assists engineers, technicians and construction managers in the prevention and treatment of structural failures, promoting greater durability, safety and performance of buildings. The research develops an in-depth analysis of the pathologies that compromise the durability, safety and structural performance of buildings, combining a specialized bibliographic review, analysis of ABNT technical standards and empirical application through a case study in a medium-sized commercial building located in Espírito Santo. The methodology adopted is qualitative, descriptive and applied, involving documentary survey and technical inspection based on current normative parameters. The results reveal that flexural cracks, corrosion of reinforcements, poor concreting, segregation and undesigned perforations are the most recurrent anomalies, often resulting from executive failures, lack of inspection and negligence in preventive maintenance. The analysis of the case study reinforces the importance of a rigorous technical diagnosis, project compatibility and professional training as fundamental measures to prevent premature deterioration of structures. It is concluded that diagnostic engineering integrated with maintenance management is essential to guarantee the safety, durability and sustainability of reinforced concrete buildings in the Brazilian context.